Plasma fibronectin is a prognostic biomarker of disability in Parkinson’s disease: a prospective, multicenter cohort study - Shuzhen Zhu; Hualin Li; Zifeng Huang; Yiheng Zeng; Jianmin Huang; Guixia Li; Shujuan Yang; Hang Zhou; Zihan Chang; Zhenchao Xie; Rongfang Que; Xiaobo Wei; et al. (npj Parkinson's Disease)
Abstract In a prospective longitudinal study with 218 Parkinson’s disease (PD) patients in the discovery cohort and 84 in the validation cohort, we aimed to identify novel blood biomarkers predicting disability milestones in PD. Through Least Absolute Shrinkage and Selection Operator-Cox (Lasso-Cox) regression, developed nomogram predictive model and Linear mixed-effects models, we identified low level of plasma fibronectin (pFN) as one of the best-performing risk markers in predicting disability milestones. A low level of pFN was associated with a short milestone-free survival period in PD. Longitudinal analysis showed an annual decline in the rate of pFN was significantly associated with the annual elevation rate in the Hoehn-Yahr stage. Moreover, pFN level was negatively correlated with phosphorylated α-synuclein, and a low level of pFN was associated with BBB disruption in the striatum on neuroimaging, providing evidence for pFN’s role in PD progression. We finally identified pFN as a novel blood biomarker that predicted first-milestone disability in PD.